Model Based Transformation of Students Examination Scores and Assessment of Changes in Grade Point Average - Udokang, A. E.; Abdulqodir, H. D.; Abdulkareem, S. O.; Okeniyi, O. M. (NIU Journal of Humanities, 2019)
It is often desired to gear up studentsâ€™ examination scores when performance is very poor and it is required to comply with NBTE/NUC 75% pass requirements.  A categorical flow of studentsâ€™ grade point average (GPA) is also desired when effort is being made to achieve objectives of counseling exercises.  Towards these ends, this paper was intended to provide methods of score up grading and assessing changes in GPA. A two-edge linear transformation was proposed for gearing up scores.  Assumptions of Markov chains and outfit of Grendenko sequence were up held to develop GPA transition matrix.  Chai-square test was incorporated to ensure stationary transition and flow of GPA from one categorical level to another.  Application of results carried out on different sets of two consecutive session examination results revealed that many of the students concerned had worked harder to justify movement of GPA from pass grade to lower credit grade. In some cases, performance could not be improved from lower credit grade to upper credit grade and no case of improvement from upper credit grade to distinction was revealed. Keywords: Base-upper score limits; Markov chains principle; Grendenko estimating sequence; Stationary transition; Categorical flows.